Educación superior intercultural : en busca de la universidad intercultural. (2013)
This article presents some of the main results of the research titled as “superior intercultural Education: searching the intercultural university”. This is based on the study and the critical analysis of emerging intercultural universities in our contemporary context characterized, in words of Wallerstein, by the structural crisis of the capitalist world system. In addition, from a hegemonic view, this study widens the understanding of the educational process in the indigenous communities. Thus, this text has reviewed the importance of the different epistemologies and the diversity of ways to produce knowledge in the indigenous communities from Latin America.